2017
DOI: 10.1080/09658211.2017.1283420
|View full text |Cite|
|
Sign up to set email alerts
|

Priming, not inhibition, of related concepts during future imagining

Abstract: Remembering the past and imagining the future both involve the retrieval of details stored in episodic memory and rely on the same core network of brain regions. Given these parallels, one might expect similar component processes to be involved in remembering and imagining. While a strong case can be made for the role of inhibition in memory retrieval, few studies have examined whether inhibition is also necessary for future imagining and results to-date have been mixed. In the current study, we test whether r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
(74 reference statements)
2
4
0
1
Order By: Relevance
“…The increase in false memories when imagining the future is also consistent with the recent finding by Campbell et al (2017) that related concepts are automatically activated when simulating a future event. Whereas successful remembering often requires the inhibition of related concepts in tasks such as retrieval-induced forgetting (Anderson et al, 1994), Campbell et al found no evidence of inhibition of related concepts when imagining future events.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increase in false memories when imagining the future is also consistent with the recent finding by Campbell et al (2017) that related concepts are automatically activated when simulating a future event. Whereas successful remembering often requires the inhibition of related concepts in tasks such as retrieval-induced forgetting (Anderson et al, 1994), Campbell et al found no evidence of inhibition of related concepts when imagining future events.…”
Section: Discussionsupporting
confidence: 89%
“…This greater flexibility enhanced the associative processes that give rise to false memories in the DRM paradigm, thereby increasing the likelihood that critical lures were activated at study and, subsequently, falsely remembered at test. This interpretation is consistent with findings recently reported by Campbell, Benoit, and Schacter (2017), who investigated the effects of inhibition on imagining the future. As Campbell et al observed, tasks such as retrieval-induced forgetting show that successful retrieval often requires the inhibition of related concepts (see Anderson, Bjork, & Bjork, 1994).…”
supporting
confidence: 93%
“…More generally, the capacity to represent and generate experiential explanations seems to be in some way connected to the ability to simulate. For instance, there is a well‐documented connection between episodic memory and imaginative future thinking, including a shared neural basis for both in the hippocampus (Campbell, Benoit, & Schacter, 2017; Parikh, Ruzic, Stewart, Spreng, & De Brigard, 2018). One way of reading this connection is what Schacter and Addis (2007) call the Constructive Episodic Simulation Hypothesis , on which a single cognitive system is responsible for constructing past scenes, future predictions, and imagined alternative possibilities.…”
Section: Advantages Of Experiential Explanationmentioning
confidence: 99%
“…May be enhanced by human experience "exploring; hands on" art of the possible; interaction with others (Tulving and Murray 1985) Likelihood of the probable based on massive inventory of science, data, and known facts (Campbell et al 2017).…”
Section: Neuroscience and Futures May Be Complementary In Helping Us mentioning
confidence: 99%
“…2 Functional MRI (magnetic resonance imaging) as opposed to static MRI allows brain functions to be seen in real time through active blood flow. According to new data by using of episodic memory and semantic memory (Tulving and Murray 1985), the same regions of the brain appear to be active when we think of the past and when we think of the future (Campbell et al 2017). Atance and O'Neill (2001) have built upon Tulving's work on episodic memory.…”
Section: Neuroscience Opens Insights To "Using the Future"mentioning
confidence: 99%